After-Tax Discounting: A Research Edge - Hongtao Guo (Journal of Accounting, Business and Management (JABM), 2020)
This research note addresses after-tax discounting for pricing assets. Specifically, it analyzes the appropriate way to discount after-tax payoffs from assets that trade in capital markets in which both taxable and tax-free investors can buy and sell both taxable and tax-free instruments. The effect of the tax status of the investor and the tax status of the financing tool that an investor uses on price of an asset are discussed. Secondly, it derives the proper after-tax discount rate to use in the risk neutral valuation method for pricing assets that have state-contingent payments, typically structured in a lease based transaction. Dynamic state-contingent payoffs and cash flow processes are developed. Pre-tax discounted price, after-tax discounted payoffs are considered, then after-tax discount rate is derived. Included in this analysis of state-contingent discounting is the effect of depreciation expense, the only expense associated with the use of the asset, on after-tax discount rates.